Lipid Levels and Lung Cancer Risk: Findings from the Taiwan National Data Systems from 2012 to 2018 - Jung-Yueh Chen; Nai-Hui Chi; Ho-Shen Lee; Chia-Ni Hsiung; Chang-Wei Wu; Kang-Chi Fan; Meng-Rui Lee; Jann-Yuan Wang; Chao-Chi Ho; Jin-Yuan Shih (Journal of Epidemiology and Global Health, 2025)
Abstract Background Lipids are known to be involved in carcinogenesis, but the associations between lipid profiles and different lung cancer histological classifications remain unknown. Methods Individuals who participated in national adult health surveillance from 2012 to 2018 were included. For patients who developed lung cancer during follow-up, a 1:2 control group of nonlung cancer participants was selected after matching. Multivariate conditional logistic regression was used to explore the associations between lipid profiles, different lung cancer histological classifications and epidermal growth factor receptor mutation statuses. Subgroup, sensitivity, and dose‒response analyses were also performed. Results A total of 4,704,853 participants (30,337 lung cancer participants and 4,674,516 nonlung cancer participants) were included. In both the main and sensitivity analyses, the associations remained constant between lower high-density lipoprotein (HDL) cholesterol levels and a higher risk of lung cancer (main analysis: odds ratio: 1.13 [1.08–1.18]) and squamous cell carcinoma (1.29 [1.16–1.43]). Hypertriglyceridemia was associated with a lower risk of adenocarcinoma (0.90 [0.84–0.96]) and a higher risk of small cell lung cancer (1.31 [1.11–1.55]). Hypercholesterolemia was associated with a lower risk of squamous cell carcinoma (0.84 [0.76–0.94]). In the subgroup analysis, lower HDL cholesterol levels were associated with greater risk across most subgroups. HDL cholesterol levels also demonstrated a dose‒response association with the development of lung cancer. Conclusions The distinct associations between specific lipid profiles and lung cancer subtypes suggest that lipid metabolism may play different mechanistic roles in lung cancer development.